Blocking ATM Attenuates SKOV3 Cell Proliferation and Migration by Disturbing OGT/OGA Expression via hsa-miR-542-5p - Wang, Ning; Yu, Miaomiao; Fu, Yan; Ma, Zhanchuan (Frontiers in Oncology, 2022)
Blocking ataxia telangiectasia mutated (ATM), a crucial player in DNA repair responses, has been proposed as a promising strategy in anti-cancer therapy. Most previous studies have focused on DNA damage response-related pathways after administration of ATM inhibitors. However, ATM inhibition could potentially influence a wide range of changes in gene expression, which remain poorly defined. Here, we report that administration of the ATM inhibitor KU60019 led to impaired migration and enhanced apoptosis in the ovarian cancer cell line SKOV3, accompanied by abnormally elevated O-GlcNAc transferase and O-GlcNAcase expression levels. In addition, KU60019 treatment significant suppressed expression of hsa-miR-542-5p in SKOV3 cells. Up-regulation of hsa-miR-542-5p expression inhibited increases in OGT and OGA level, and reversed the effects of ATM inhibition on apoptosis and migration in SKOV3 cells. Finally, we found aberrant expression of OGT and OGA to be associated with ovarian cancer patient survival. Taken together, our results suggest that ATM inhibition may promote SKOV3 cell apoptosis via suppressing hsa-miR-542-5p and elevating OGT and OGA expression, providing new insights into the application of ATM inhibitors in cancer immunotherapy.